Testing and tracking with Asa G. Hilliard, III - National Association for the Education of Young Children (The association, 1989)
El profesor Asa G. Hilliard de la Urban Education, Georgia State University expone sobre "Evaluación curricular". Barbara Bowman del Erikon Institute, Patty Calvert de la American Montessori Society y Constance Kamii de University of Alabama.